2018
DOI: 10.1007/s00705-018-3769-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of the green tea molecule EGCG against dengue virus infection

Abstract: Dengue virus (DENV) infection is a major public health problem worldwide; however, specific antiviral drugs against it are not available. Hence, identifying effective antiviral agents for the prevention of DENV infection is important. In this study, we showed that the reportedly highly biologically active green-tea component epigallocatechin gallate (EGCG) inhibited dengue virus infection regardless of infecting serotype, but no or minimal inhibition was observed with other flaviviruses, including Japanese enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Catechins as a class of polyphenolic flavonoids are the main active ingredients of green tea as well as many other teas, which among other properties can strengthen the immunity against viral, especially influenza infections (141). The most prominent of these, epigallocatechin gallate (EGCG), even inhibited dengue virus infection in vitro regardless of the serotype and at concentrations reasonable for pharmacological application (142). Several epidemiological studies have suggested that regular consumption of green tea decreases influenza infection rates (143), while clinical trials have mostly used standardized catechin extracts.…”
Section: Green Teamentioning
confidence: 99%
“…Catechins as a class of polyphenolic flavonoids are the main active ingredients of green tea as well as many other teas, which among other properties can strengthen the immunity against viral, especially influenza infections (141). The most prominent of these, epigallocatechin gallate (EGCG), even inhibited dengue virus infection in vitro regardless of the serotype and at concentrations reasonable for pharmacological application (142). Several epidemiological studies have suggested that regular consumption of green tea decreases influenza infection rates (143), while clinical trials have mostly used standardized catechin extracts.…”
Section: Green Teamentioning
confidence: 99%
“…In 2018, Raekiansyah et al [24] reported that EGCG ( 1 ) inhibited DENV infection regardless of the infecting serotype and the 50% effective concentration of EGCG in Vero cells was estimated to be approximately 14.8 μM, 18.0 μM, 11.2 μM, and 13.6 μM for DENV-1, DENV-2, DENV-3, and DENV-4, respectively. However, no or minimal inhibition was observed with other flavivirus, including JEV, YFV, and ZIKV, contradicting previous reports by Carneiro [20] and Vázquz-Calvo [23].…”
Section: Antiviral Activity Of Catechins On Enveloped (+) Ssrna VImentioning
confidence: 99%
“…Regarding these biological properties, EGCG ( 1 ) has been reported to possess a broad spectrum of antiviral activities against DNA viruses such as herpes simplex virus (HSV; Herpesviridae ) [5,6,7,8,9,10,11], adenovirus ( Adenoviridae ) [10,12], human papilloma virus (HPV; Papovaviridae ) [13], and hepatitis B virus (HBV; Hepadnaviridae ) [14], and against (+)-RNA viruses such as hepatitis C virus (HCV; Flaviviridae ) [10,15,16,17,18,19], Zika virus (ZIKV; Flaviviridae ) [20,21,22,23], dengue virus (DENV; Flaviviridae ) [23,24], West Nile viruses (WNV; Flaviviridae ) [23], Chikungunya virus (CHIKV; Togaviridae ) [25], and Porcine Reproductive and Respiratory virus (PRRS; Atteriviridae ) [26], and (−)-RNA viruses such as human immunodeficiency virus (HIV; Retroviridae ) [27,28,29,30,31,32,33,34,35,36], Ebola virus (EBOV; Filoviridae ) [37] and influenza virus ( Orthomyxoviridae ) [2,10,38,39,40,41,42,43,44,45,46,47,48]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that catechins, particularly EGCG, have antimicrobial (Gram-positive and Gram-negative bacteria) ( 87 ) and antiviral activities with different modes of action ( 202 ). The negative effects of catechins were reported, mostly in cultured cells, against a wide range of DNA viruses, including HSV ( 43 , 172 ), human papillomavirus ( 90 ), and hepatitis B virus ( 91 ); against (+)-RNA viruses such as HCV ( 23 ), ZIKV ( 29 , 220 ), DENV ( 173 ), West Nile viruses ( 220 ), Chikungunya virus (CHIKV; Togaviridae) ( 141 ), and porcine reproductive and respiratory virus ( 245 ); and against (−)-RNA viruses such as HIV ( 131 ), Ebola virus ( 180 ), and influenza virus ( 188 ).…”
Section: Antiviral Activities Of Polyphenolsmentioning
confidence: 99%